If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -3)(y + 6) = 0 Reorder the terms: (-3 + x)(y + 6) = 0 Reorder the terms: (-3 + x)(6 + y) = 0 Multiply (-3 + x) * (6 + y) (-3(6 + y) + x(6 + y)) = 0 ((6 * -3 + y * -3) + x(6 + y)) = 0 ((-18 + -3y) + x(6 + y)) = 0 (-18 + -3y + (6 * x + y * x)) = 0 (-18 + -3y + (6x + xy)) = 0 Reorder the terms: (-18 + 6x + xy + -3y) = 0 (-18 + 6x + xy + -3y) = 0 Solving -18 + 6x + xy + -3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 6x + xy + 18 + -3y = 0 + 18 Reorder the terms: -18 + 18 + 6x + xy + -3y = 0 + 18 Combine like terms: -18 + 18 = 0 0 + 6x + xy + -3y = 0 + 18 6x + xy + -3y = 0 + 18 Combine like terms: 0 + 18 = 18 6x + xy + -3y = 18 Add '3y' to each side of the equation. 6x + xy + -3y + 3y = 18 + 3y Combine like terms: -3y + 3y = 0 6x + xy + 0 = 18 + 3y 6x + xy = 18 + 3y Reorder the terms: -18 + 6x + xy + -3y = 18 + 3y + -18 + -3y Reorder the terms: -18 + 6x + xy + -3y = 18 + -18 + 3y + -3y Combine like terms: 18 + -18 = 0 -18 + 6x + xy + -3y = 0 + 3y + -3y -18 + 6x + xy + -3y = 3y + -3y Combine like terms: 3y + -3y = 0 -18 + 6x + xy + -3y = 0 The solution to this equation could not be determined.
| 4/15/5/7 | | -1/2x-2=0 | | P=5Q+7 | | 4x^2+19x-23=0 | | (x+2)(y+4)= | | X-94=-5x+2 | | X^4-10x-50=0 | | Y-C=S | | .5x=197125 | | .05x=197125 | | 3/11 | | -2(3n+2)=4 | | y^2+6y-28=0 | | 8(y-5)/3=-2y | | 3.14*100*h=4710 | | X(7.8-1.2)=54.2 | | (2x+13)(x-3)=0 | | Y=38+7.7x | | log(x+13)-log(2)=log(3x+3) | | 7x=28000000 | | 0.60x+0.85*30=0.30*97 | | 2(6x-13)= | | log(x+13)-log(2)=log(2x+3) | | 43-2[6+(3+2)]= | | 0.03x+0.15(70)=0.15(82) | | 2x+x+6=8 | | Sin(2x)cos(x)=sin(x)cos(2x) | | -4/5(-19/16) | | 12+3[5+(4-2)]= | | |-5|= | | 0.0003x^2+2x+300= | | |11|= |